Nanoelectronics with CMOS transistors: electrostatic and quantum effects. (22nd February 2010) - Jehl, Xavier; Sanquer, Marc; Gautier, J.; Vinet, M.
In this contribution, we review the differences and similarities between the field effect transistor (FET) and the single electron transistor (SET) made of silicon. We show that there is a convergence in both types of devices when shrinking the dimensions and this convergence is driven by the value and the nature of the access resistances to the channel. Access resistance above the quantum of resistance will produce single electron effects in the channel and this is illustrated in the case of a non-overlapped geometry for silicon nanowire MOSFETs. Considerations about the origin of the intrinsic resistance of the access regions and about their variability are also presented. We expect future generations of MOSFET to exhibit more and more the reported SET effects due to the high resistance of their ultra-scaled nano-access.